Determinação do índice de estresse hídrico em cultura do feijoeiro com termômetro de infravermelho - Fernandes, Edemo João [UNESP] (My University, 2010)
In order to calculate the daily stress degree of a bean crop submitted to four water regime applications, cover crop and air daily measurements temperatures were accomplished by using a hand-held infrared thermometer. The treatments did not present crop water stress except the control (without irrigation). The highest yield was obtained by the treatment that received less irrigation frequency, and among the treatments that had the same number of irrigation. The largest yield was obtained with the one that received larger amount of applied water. The largest irrigation frequency did not result in larger productivity. The methodologies used for the irrigation planning were efficient for the replacement of soil water. The daily stress degree index was effective in determining crop water stress; and it was reliable presenting negative values in good water soil condition.

Por intermédio de um termômetro infravermelho portátil foram realizadas leituras diárias de temperaturas da cobertura vegetal e do ar em cultura do feijoeiro submetida a quatro regimes de dotação hídrica, a fim de se calcular o Índice de Estresse Hídrico Diário (IEHD). Com exceção da Testemunha (sem irrigação), todos os outros regimes de aplicação de água não ocasionaram estresse hídrico na cultura. A maior produtividade foi obtida pelo tratamento que teve o menor número de irrigações e, entre os tratamentos que tiveram o mesmo número de irrigações, a maior produtividade foi obtida com o que recebeu maior quantidade de água aplicada. A maior freqüência de aplicação de água não resultou em maior produtividade. As metodologias utilizadas para o planejamento das irrigações foram eficientes para a reposição de água no solo. O índice de estresse hídrico diário (IEH) foi eficaz na indicação do estresse hídrico da cultura, apresentando sempre valores negativos em condições de umidade do solo favorável ao desenvolvimento da cultura.
Water stress index determination on bean crop with infrared thermometry
Keywords: Bean; Infrared thermometer; Irrigation; Water stress; crop yield; index method; irrigation system; legume; measurement method; water stress; water temperature